Road to green urbanization: how does urbanization process affect the green land use efficiency - Yang, Ruoxi; Wang, Jiayao; Xu, Minghao; Xu, Ke (Frontiers in Environmental Science, 2025)
IntroductionAs the process of urbanization accelerates, high energy consumption, pollution, and low land use efficiency have led to many significant negative impacts on production and daily life.MethodsIn order to investigate the impact of urbanization construction on green land use efficiency and its potential mechanisms, the indicators of China’s urbanization evaluation system are constructed, and the SBM-GML model is used to measure green land use efficiency. Based on this, data from 30 provinces in China from 2013 to 2023 are used to test them using fixed effects, mediating effects and threshold effects.Results(1) The construction of the urbanization process can directly contribute to the improvement of green efficiency in land use. This conclusion remains valid after conducting endogeneity and robustness tests. (2) The mediating effect test shows that the urbanization process can increase synergistic industrial agglomeration and promote the optimization of the industrial structure, thus indirectly promoting the improvement of green land use efficiency. (3) The threshold effect test shows that a threshold effect exists in the relationship between the level of economic development and green land use efficiency, based on the urbanization process. As urbanization deepens, the role of economic development in improving green land use efficiency gradually strengthens. (4) Heterogeneity analysis reveals that the construction of the urbanization process has a more significant impact on driving green land use efficiency in cities in eastern China.DiscussionThis paper suggests optimizing the allocation of land resources in the process of accelerating urbanization and improving the efficiency of land use in terms of green. Attention should be given to the regional differences in carbon emissions during urbanization, and it is essential to continuously optimize the realized low-carbon urbanization model. Special attention should be paid to enhancing carbon emission control in underdeveloped regions, in order to promote the nationwide improvement of green land use efficiency.